The effect on unfavourable economic conditions in Malaysia to abandoned housing project - Nur Farhayu, Ariffin; Saidah Annisaa, Salam; Adib Danial, Kamaruddin
Abandoned of housing projects during constructionis a prevailing problem that the housing sector in Malaysia has been experiencing since 1980s. This paper aims to highlight the causes and impacts of economic growth towards the abandoned housing projects. Factors pertaining to projects abandonment can be categorized into economic, financial, legal, managerial, system-related, and unforeseen risks. The study reveals mainimpacts of abandoned housing projects which is economic impacts. For this purpose, the study looks into how the extent of the impact of rising raw material prices, labour wage prices and transport machinery prices especially in Peninsular Malaysiatowards the growth of number in abandoned housing project.